The definition and taxonomy of collaborative housing as bottom-up and community-based forms of meeting housing needs in Poland - Rataj, Zuzanna (Research Papers in Economics and Finance, 2023)
The concept of collaborative housing emerged in Poland less than a decade ago. From the historical perspective, living in a community has a long tradition. In Poland, the first projects operating similarly to collaborative housing initiatives emerged right after World War I, when destroyed cities experienced scarcity of flats and houses. Currently, the form and conditions to be met by pro- jects in order to be classified into collaborative housing as under- stood nowadays are changing. The concept is based on collaborative housing projects successfully operating in the countries of Western Europe. In Poland, only few such investments have been established (Nowe Żerniki, Kooperatywa Mieszkaniowa Pomorze and Kooperatywa Mieszkaniowa Konstancin – this project is constructed with support of Habitat for Humanity Poland). In the face of the ongoing socioeconomic changes, however, they might become an interesting alternative to commercial housing construction.